Pigmented eccrine poroma: report of an atypical case with the use of dermoscopy - Fabiana Carvalho de Almeida; Silvana Maria de Morais Cavalcanti; Angela Cristina Rapela Medeiros; Marcia Almeida Galvao Teixeira (Sociedade Brasileira de Dermatologia, 2013)
Poromas are uncommon benign neoplasms originating from the terminal ductal portion of the sweat glands, mainly characterized by skin-colored or pink pa pules or nodules, usually on the extremities. Due to their rarity, the pigmented form clinical hypothesis is hardly ever suggested and psychopathology is fundamental. We report a case of pigmented eccrine poroma in the right palmer area, a location considered atypical. We stress the importance of dermoscopy as a method for diagnosis of poromas, especially in the differential diagnosis with other pigmented nodular-popular lesions.